The Comparative Study of Students Learning Styles Towards Their Ability in Grammar - Sukra Titin Sholeha; Hilma Pami Putri; Syahrul Syahrul; Loli Safitri (Education Achievement: Journal of Science and Research, 2024)
This research was purposed to discover students’ learning style and the differences of students’ grammar ability among the visual, auditory and kinesthetic learning style. The research followed comparative quantitative design. The participants of the research were 83 students of the sixth semester of English education department of State Islamic University of Sjech M. Djamil Djambek Bukittinggi. Data were collected by using questionnaire and documentation. Data analysis was conducted using descriptive statistical analysis of SPSS program after scoring the respondents’ questionnaire response by Likert scale point and calculating students’ final score of grammar subject. The results revealed the dominant style that students have are visual, auditory and kinesthetic learning style and visual style as the majority. The compared students’ grammar final score exhibited differences of students’ grammar ability. Students with kinesthetic learning style obtained the highest score (88,72) and also the lowest score (66) than visual and auditory learning style. The highest mean score was obtained by auditory learning style (82,33). In conclusion, students’ grammar ability was significantly different among the students with visual, auditory and kinesthetic learning style.